A DFT treatments for studying the vibration frequencies and normal coordinates of cyclacene molecules with different diameters (Unit Construction of ZigZag SWCNTs) - Rehab M. Kubba (Iraqi Journal of Physics, 2012)
Semi-empirical methods (MINDO/3, PM3) and Density Functional Theory calculations (DFT/ B3LYP/ 6-311G) were carried out to evaluate the vibration frequencies and Infra-Red (IR) absorption intensities for equilibrium geometries, of 6,7,8,10 and 12 cyclacene's molecules of different diameters for (SWCNTs). The Gaussian 03 and MOPAC computational packages have been employed throughout this study to compute the geometrical Parameters (bond lengths and bond angles) and the energetic properties, (vibration frequency, heat of formation and electronic charge distribution for the modeled 6,7,8,10 and 12 cyclacene's molecules of different diameters nanostructures (zig-zag). The results include the assignment of all puckering, breathing and clock-anticlockwise bending vibrations. They allow a comparative view of the charge density at the carbon atom too. According to the group theory and character tables all the irreducible representations of the vibration were assigned. The comparison of the calculated models revealed general correlations among the frequencies of (CH and CC) stretching vibration modes, the diameter and chirality.